The Myth for Almada Negreiros - Carvalho, João Pedro (2023)
This essay analyses the concept of “myth” in Almada Negreiros, focusing on Myth-Alegory-Symbol to harmonize diverse mythopoetical manifestations in his works. The mythological thought of Almada is contextualized inside the mission that he gives the artist: as an example of radical individuality and as a reformer of the collectivity; recovering the power that myth had in the formation of the individual and the nation to transfigure them in the 20th century, by updating them.